Small-worldness characteristics and its gender relation in specific hemispheric networks. (3rd December 2015) - Miraglia, F.; Vecchio, F.; Bramanti, P.; Rossini, P.M.
Highlights: Graph theory approach as a way to quantify brain connectivity. Gender small-worldness differences in EEG resting state networks. Resting state networks: Attentional, Frontal, Sensorimotor, Default Mode Network. Abstract: Aim of this study was to verify whether the topological organization of human brain functional networks is different for males and females in resting state EEGs. Undirected and weighted brain networks were computed by eLORETA lagged linear connectivity in 130 subjects (59 males and 71 females) within each hemisphere and in four resting state networks (Attentional Network (AN), Frontal Network (FN), Sensorimotor Network (SN), Default Mode Network (DMN)). We found that small-world (SW) architecture in the left hemisphere Frontal network presented differences in both delta and alpha band, in particular lower values in delta and higher in alpha 2 in males respect to females while in the right hemisphere differences were found in lower values of SW in males respect to females in gamma Attentional, delta Sensorimotor and delta and gamma DMNs. Gender small-worldness differences in some of resting state networks indicated that there are specific brain differences in the EEG rhythms when the brain is in the resting-state condition. These specific regions could be considered related to the functions of behavior and cognition and should be taken into account both for research on healthy and brain diseased subjects.